Direct arylation of imidazo[2, 1‐b]thiazoles and thiazoles with aryl iodides via CuCl2/PPh3‐catalyzed C–H bond functionalization. (15th January 2015) - Ma, Yuchang; Na, Min; Gu, Yanfang; Huang, Guoli; Li, Xia; Chen, Yegao
<x xml:space="preserve">Abstract</x> With PPh3 acting as a ligand, a convenient method for CuCl2‐catalyzed arylation of imidazo[1, 2‐b]thiazoles and thiazoles with aryl iodides under mild reaction conditions is described. Preliminary mechanistic studies of this arylation involving a formal Cu(I) to Cu(0) and Cu(II) route by convergent disproportionation of the copper mediator are also reported. Copyright © 2015 John Wiley & Sons, Ltd.